Śmierć Józefa Piłsudskiego w wybranych tytułach prasy amerykańskiej - Różański, Przemysław (Dzieje Najnowsze, 2015)
The Death of Józef Piłsudski in Selected Examples of the American Press In the USA the death of Józef Piłsudski produced an out of the ordinary reaction in the mass media. This thesis is confirmed by an analysis of selected titles of the opinion–forming American press and reports by Stanislaw Patek, Ambassador of the Republic of Poland to the American government. Systematic analyses encompass the following dailies published in the US: “New York Times”, “Chicago Daily Tribune”, “Los Angeles Times”, “Atlanta Constitution” and “Washington Post”. The significance attributed by the American press to the death of the first Marshal of Poland is evidenced by the presence of pertinent editorials. Moreover, information about Piłsudski’s death was published on the front pages of the above–mentioned periodicals, which also included biogrammes of the Marshal of Poland. American publicistics studied in the article can be divided into: (1) texts informing about the death of Piłsudski, (2) biogrammes, (3) articles on the hypothetical external and domestic consequences of the death of the Polish leader, (4) editorials, and (5) feature articles about the funeral ceremonies of the Polish politician. These texts, often written by the most outstanding American journalists, created a decidedly favourable portrait of the Polish leader – a patriot who devoted his whole life to a struggle for an independent Poland, a victorious commander in the Polish–Bolshevik war, and, finally, a dictator who preserved the civic liberties of the Poles.